The upper Coniacian to upper Santonian drowned Arabian carbonate platform, the Mardin-Mazidag area, SE Turkey: Sedimentological, stratigraphic, and ichthyofaunal records. (April 2018) - Yilmaz, Ismail O.; Cook, Todd D.; Hosgor, Izzet; Wagreich, Michael; Rebman, Katherine; Murray, Alison M.
Abstract: A measured stratigraphic section including the upper Coniacian – upper Santonian interval in the Mardin-Mazidag area in Southeastern Turkey lies on the Arabian Platform and documents the drowning of the Arabian platform. The studied succession transgressively overlies the exposed carbonate platform and exhibits a relatively condensed sequence characterized by presence of fish remains, phosphate nodules, oncoids, phosphatic fragments, glauconites and planktonic foraminifera. Calcareous nannofossils attest a late Coniacian to late Santonian age (zones UC11 UC12). Numerous elasmobranch teeth are also present in this pelagic facies, representing mackerel sharks ( Squalicorax, Pseudocorax and Scapanorhynchus ) and a ray ( Ctenopristis ). The presence of pelagic facies and phosphate deposits on the drowned platform may indicate a sudden rise of sea level and increase of nutrient due to upwelling currents. The collapse parts of the Arabian carbonate platform occurred earlier than previously reported, starting from late Coniacian-Santonian onwards. Graphical abstract: Highlights: The carbonates of the Karababa Formation on the Arabian platform have been studied. Late Coniacian – Late Santonian interval displays drowning of the Arabian platform. The succession presents fish remains, phosphatic fragments and glauconites. Ctenopristis jordanicus found likely endemic to the Near East. An oceanic and biogeographic connection with European/Mediterranean Tethys oceans.